Differential localization of PER1 and PER2 in the brain master circadian clock. (8th November 2016) - Riddle, Malini; Mezias, Erica; Foley, Duncan; LeSauter, Joseph; Silver, Rae
Abstract: The hypothalamic suprachiasmatic nucleus (SCN), locus of the master circadian clock, bears many neuronal types. At the cellular–molecular level, the clock is comprised of feedback loops involving 'clock' genes including Period1 and Period2, and their protein products, PERIOD1 and PERIOD2 (PER1/2). In the canonical model of circadian oscillation, the PER1/2 proteins oscillate together. While their rhythmic expression in the SCN as a whole has been described, the possibility of regional differences remains unknown. To explore these clock proteins in distinct SCN regions, we assessed their expression through the rostro‐caudal extent of the SCN in sagittal sections. We developed an automated method for tracking three fluorophores in digital images of sections triply labeled for PER1, PER2, and gastrin‐releasing peptide (used to locate the core). In the SCN as a whole, neurons expressing high levels of PER2 were concentrated in the rostral, rostrodorsal, and caudal portions of the nucleus, and those expressing high levels of PER1 lay in a broad central area. Within these overall patterns, adjacent cells differed in expression levels of the two proteins. The results demonstrate spatially distinct localization of high PER1 vs. PER2 expression, raising the possibility that their distribution is functionally significant in encoding and communicating temporal information. The findings provoke the question of whether there are fundamental differences in PER1/2 levels among SCN neurons and/or whether topographical differences in protein expression are a product of SCN network organization rather than intrinsic differences among neurons. Abstract : The photomicrograph shows a triply labeled sagittal section through the entire rostro‐caudal extent of the SCN, labeled for PER1 and PER2 protein at their times of peak expression. Automated analysis of the topography of protein expression is shown in contour diagrams highlighting broad regions with differential expression of PER1 and PER2. Individual cells expressing one but not the other PER protein were commonly seen within these broad regions. Mag bar = 100 μm.